Proceso de atención de enfermería en gestante de 38 años con preeclampsia. - Icaza León, Paola Elizabeth (2021)
The study that was carried out in a clinical case that was presented on the basis of a pregnant patient with pre-eclampsia in which the Nursing Care Process was applied, which aimed to apply the PAE. We must understand that preeclampsia is one of the major complications that is evident in pregnant patients, which were based on the increase in blood pressure above its normal range, in addition to causing damage to other organs, where the most affected usually be the liver and renal system alterations. In this study, the clinical case of a pregnant patient with pre-eclampsia who presented a clinical picture of 24 hours of evolution, characterized by presenting hypogastric pain, headache, was carried out, a rapid evaluation was carried out where there was evidence of elevation of the arterial pressure (hypertensive picture) in addition, edemas are observed in the inferior extremities, afebrile. The clinical part determined the degree of preeclampsia that the patient suffered, through complementary tests that served to assess functional patterns and establish the nursing diagnosis of the ineffective maternity process and risk of maternal / fetal alteration, it is important to indicate that the application of the Nursing care process with the taxonomy of NANDA, NIC, NOC and the functional patterns of Marjory Gordon allowed the recovery of the patient.